2018
DOI: 10.2147/cmar.s164535
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-related adverse effects with pazopanib, sorafenib and sunitinib in patients with advanced soft tissue sarcoma: a pooled analysis

Abstract: ObjectiveResearch efforts have investigated therapies targeting tyrosine kinase signaling pathways. We performed a pooled analysis to determine the frequency of severe adverse effects in patients with soft tissue sarcoma treated with pazopanib, sorafenib and sunitinib.Materials and methodsWe performed a comprehensive search of PubMed, Web of Science, Ovid, the Cochrane Library and Embase databases from the drugs’ inception to May 2017 to identify clinical trials. All-grade and severe adverse events (AEs; grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…In this study, we investigated the preventive effects of prophylactic RJ consumption on AEs associated with TKI-induced toxicities because the appropriate management of these AEs is critical for maintaining quality of life in RCC patients treated with TKIs. Various harmful symptoms and abnormal observations are known as adverse events of TKIs [12,14,15,16,17,18]. Among these chemotherapy-induced symptoms, such as oral mucositis, anorexia, digestive symptoms, fatigue, and damage of the kidneys and liver, few have been shown to be suppressed by RJ administration in animal experiments and clinical trials [27,28,29,30,31,32,33,34,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated the preventive effects of prophylactic RJ consumption on AEs associated with TKI-induced toxicities because the appropriate management of these AEs is critical for maintaining quality of life in RCC patients treated with TKIs. Various harmful symptoms and abnormal observations are known as adverse events of TKIs [12,14,15,16,17,18]. Among these chemotherapy-induced symptoms, such as oral mucositis, anorexia, digestive symptoms, fatigue, and damage of the kidneys and liver, few have been shown to be suppressed by RJ administration in animal experiments and clinical trials [27,28,29,30,31,32,33,34,37].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, axitinib and sorafenib are also used in some patients with metastatic RCC [12,13]. Typical AEs linked to these TKIs include various symptoms such as oral mucositis, hand–foot syndrome, hypertension, fatigue, and gastrointestinal events [14,15,16,17,18]. In addition, functional disorders of the kidneys, liver, and thyroid are often associated with TKIs [14,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, transforming growth factor (TGF)-β1 is known as a tumor inhibitor during the early stage of different cancers, whereas it functions as a tumor promoter (promoting tumor invasion and metastasis) during the later stages (Heldin et al 2017 ). Vascular endothelial growth factors (VEGFs) and their receptors (VEGFRs) play critical roles in angiogenesis during tumor growth and metastasis (Que et al 2018 ; Shay et al 2015 ). MMPs, known as physiologic scissors, are involved in extracellular matrix (ECM) degradation and tissue remodeling (Lee et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…25 Que et al conducted a pooled analysis with 10 trials published between 2009 and 2016, including 843 patients, and examined treatment-related adverse effects with pazopanib, sorafenib, and sunitinib in patients with advanced STS, and as a result, they did not report any cardiac severe dysfunction. 26 Conversely, Hall et al evaluated 159 patients receiving TKIs including pazopanib for the treatment of advanced RCC and showed that the cardiotoxicity related to all study drugs when hypertension was excluded varied from occurrence of asymptomatic drops in LVEF to severe HF was 33%, and the rate of decreased LVEF (grades 2-4) related only to pazopanib was 7%, which are higher than the general rates reported in the literature. Also, they concluded that in the previous studies the incidence of asymptomatic cardiovascular toxicity has not been reported and therefore, the frequency and severity of cardiovascular toxicity in their cohort were high.…”
Section: Discussionmentioning
confidence: 96%